(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lyell’s syndrome (toxic epidermal necrolysis, scalded skin syndrome) is the most severe type of allergic bullous dermatitis. Named after Scottish dermatologist Alan Lyell (1917–2007), who first made a detailed description of the disease in 1956.Most often, Lyell’s syndrome is a reaction to medications. Basically, Lyell’s syndrome develops in people with a burdened allergic history, most often against the background of an acute respiratory viral infection (ARVI), for which patients were taking medications. The patient’s condition progressively worsens, symptoms of intoxication are expressed, and the temperature rises. A skin rash appears like measles or scarlet fever with isolated painful elements. After a few hours, large flat blisters with serous or serous-hemorrhagic contents appear at the site of the rash and on previously unchanged skin. They quickly open with the appearance of extensive erosions of a bright red color. A positive Nikolsky symptom is characteristic - when healthy skin is lightly rubbed, desquamation of the epidermis occurs and the weeping surface is exposed. Toxic-allergic damage to the heart, liver, abdominal organs, and kidneys may occur. In the absence of timely emergency care, the likelihood of death is high.